Under Fire: The Falklands War and the Revival of Naval Gunfire Support. (April 2017) - Paget, Steven
The provision of naval gunfire support was an important aspect of the Falklands War. By the end of the 1970s, naval gunfire support appeared to be doomed, but its vital role during the Falklands War led to a timely reappraisal. Indeed, the use of naval gunfire support during the Iraq War in 2003 and the conflict in Libya in 2011 vindicated the revival of interest in the capability. The Falklands War provided a number of valuable lessons about the role and significance of naval gunfire support, particularly during amphibious and expeditionary operations. With the threat of defence cuts ever-present, it is important that those lessons are not forgotten.